PERAN DAN FUNGSI PEREKAM MEDIS DALAM PELAKSANAAN HOME CARE DI RUMAH SAKIT PANTI RAPIH YOGYAKARTA - , FRANSISCA LORESTI WARUWU ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: The Vision of Ministry of Health of Indonesia Republic is to make people independentin living a healthy life with the mission of improving public health. In order to realize the vision and mission, have developed various health programs including health services in houses, which is often referred to home care. The success of home care support can be reached if there is good quality,which is by establishing the medical record. To realizewell qualified medical records and its deliverance that is in accordance to default then required a health worker who has the skills and expertise called medical recorder. The presence of this profession is very supportive for home care services due to the importance of continuity of patient medical data each time get a visit from a home care team. The purpose of the study: To identify the role and function of medical recorder in relation to the home care medical records flow and medical records management in the implementation of home care in Panti Rapih Hospital Yogyakarta. Research methodology: This type of research uses a descriptive method with qualitative approaches, as well as the phenomenological research design. Object of the research is the role and function of particular medical recorder related to the flow of medical records in the implementation of home care in Panti Rapih Hospital Yogyakarta, while the subjects of study are home care teams and medical records clerk at Panti Rapih Hospital Yogyakarta. Data was collected by interview, observation, and study documentation. Results: Medical records management activities of home care at Panti Rapih Hospital Yogyakarta basically the same as outpatient medical records management. The role and functions of medical recorder related to its medical records flow are so far only play role in managing medical records such as registration, medical records and the provision of data processing. In the management of medical recorder, human resources have become the constraint at the home where the workers still often delay the process of inputting data.